2019
DOI: 10.1002/ejic.201801452
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Disproportionation of CO2 Mediated by Bimetallic Nickelate(–I)/Group 13 Complexes

Abstract: The reactivity of bimetallic nickel(–I)/group 13 complexes towards carbon dioxide is presented. Reaction of the anionic [NiML]– complexes, where M is Al or Ga, and L is {N[(o‐C6H4)NCH2PiPr2]3}3–, with CO2 (1 atm) results in reductive disproportion of CO2 to afford CO32–, NiML, and the mono‐carbonyl adducts, (CO)NiML. The (CO)NiML complexes, where M is Al, Ga, or In, were independently synthesized and characterized. The extent of CO activation varies slightly across the different group 13 ions, where the CO str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 56 publications
2
21
0
Order By: Relevance
“…The CO stretch of 1954 cm –1 for 1-CO (in THF) indicates moderate CO activation ( cf . ν CO = 2143 cm –1 for free CO) and is on par with that reported for (CO)­Ni 0 (P­(OMe) 3 ) 3 (1952 cm –1 ) and the isostructural (CO)­NiAlL complex (1953 cm –1 ). , As expected, the reduced species, [Li]­2-CO , displays a lower stretching frequency of 1930 cm –1 (THF, Δ = −24 cm –1 ).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The CO stretch of 1954 cm –1 for 1-CO (in THF) indicates moderate CO activation ( cf . ν CO = 2143 cm –1 for free CO) and is on par with that reported for (CO)­Ni 0 (P­(OMe) 3 ) 3 (1952 cm –1 ) and the isostructural (CO)­NiAlL complex (1953 cm –1 ). , As expected, the reduced species, [Li]­2-CO , displays a lower stretching frequency of 1930 cm –1 (THF, Δ = −24 cm –1 ).…”
Section: Resultssupporting
confidence: 83%
“…Because CO withdraws electron density from the Ni–Fe core, 1-CO is both easier to reduce and harder to oxidize compared to 1 . Of note, the reduction potential of 1 is milder than any of those recorded for the related Ni-group 13 compounds, NiML: −2.82 V (M = Al), −2.48 V (Ga), and −2.34 V (In). , Moreover, the oxidation of 1 occurs at a more positive potential than that for NiAlL (−0.74 V) and NiGaL (−0.57 V), while being close to that for (N 2 )­NiInL (−0.36 V). ,, …”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Other pathways were investigated (see Figure S39 in the Supporting Information) but the one reported here appears to be the most favorable. This CO 2 reduction mechanism is very different from that reported by Murray et al for a diiron–hydride complex, where the first step is a hydrogen transfer to CO 2 , or the reaction reported by Lu et al using nickelate–group 13 complexes, where a CO 2 disproportionation is observed. On the other hand, the reactivity is slightly reminiscent of what is observed in f-element chemistry, , in particular with the formation of an intermediate where CO 2 is inserted between Ir and Al, but the protonation of CO 2 and the formation of a terminal hydroxyl unit are unique.…”
Section: Resultsmentioning
confidence: 86%
“…Stoichiometric carbon dioxide disproportionation to generate CO and CO 3 2– has been demonstrated for compounds that span the transition series; however, the history of this reaction is particularly rich for well-defined molybdenum compounds . In 1974, Chatt and co-workers discovered that cis -(Me 2 PhP) 4 Mo­(N 2 ) 2 reacts with CO 2 in toluene to yield a complex believed to be (Me 2 PhP) 4 Mo­(CO 2 ) 2 .…”
Section: Introductionmentioning
confidence: 99%